Analysis Marketing Strategies Efforts to Increase Quantity Patients on Sumberglagah Hospital Mojokerto - Siti Kumaiyah; Byba Melda Suhita; Sentot Imam Suprapto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
This study aims to analyze the application of marketing strategies that have been carried out to increase the number of patients in Sumberglagah General Hospital Mojokerto. The research design used qualitative. The social situation was all the structural teams of Sumberglagah Hospital in Mojokerto. The sampling technique used Purposive sampling with the number of informants 7 people. Triangulation was carried out on 3 speakers. The research instrument was the researcher himself and the indeep interview and FGD guidelines. Data analysis uses data reduction, data presentation, data verification and data validity test. The results of the study showed that in general Sumberglagah Hospital Mojokerto in compiling a marketing plan followed the pattern and strategy of the marketing process aimed at improving quality and complete health services. The implementation of the Marketing Strategy includes types of public services with excellent services for modern leprosy care and reconstructive surgery and prosthetic services. Quantity increases occur during general patient visits. Hospital BOR has increased in general patient visits in the last 3 years. In 2016 the BOR of general patients was 67%, 2017 was 67.5% and in 2018 was 71%. While BOR for leprosy patients decreased, in 2016 amounting to 53.8% in 2017 amounting to 40.8% and in 2018 amounting to 38.08%. The increase in the number of general patients does not go hand in hand with leprosy patients. The number of leprosy patient visits actually decreased. Influence factors due to the number of leprosy, the increase in trained personnel and the stigma of the community towards leprosy. The hospital's efforts to further improve and design the promotion of health services and to innovate regarding empowering health workers that are owned related to efforts to increase the quantity of patients both non-leprosy and leprosy. Especially for leprosy cases, the mobile unit program is intensified so that privacy of leprosy clients is more accommodated